'One man's medicine is another man's poison': a qualitative study of user perspectives on low intensity interventions for Obsessive-Compulsive Disorder (OCD). Issue 1 (December 2016) - Knopp-Hoffer, Jasmin; Knowles, Sarah; Bower, Peter; Lovell, Karina; Bee, Penny
Abstract Background Low intensity interventions based on cognitive-behavioral therapy (CBT) such as computerized therapy or guided self-help can offer effective and accessible care for mild to moderate mental health problems. However, critics argue that by reducing therapist input and the level of experience of the professionals delivering therapy, low intensity interventions deprive users of critical 'active ingredients'. Thus, while demand management arguments support the use of low intensity interventions for OCD, their integration into existing mental health services remains incomplete. Studies of user views of low intensity interventions can offer valuable insights to define their role and optimize their implementation in practice. Methods Qualitative interviews (n = 36) in adults with OCD explored user perspectives on the initiation, continuation and acceptability of two low intensity CBT interventions: guided self-help (6 h of professional support) and computerized CBT (1 h of professional support), delivered within the context of a large pragmatic effectiveness trial (ISRCTN73535163). Results While uptake was relatively high, continued engagement with the low intensity interventions was complex, with the perceived limitations of self-help materials impacting on users' willingness to continue therapy. The addition of professional support provided an acceptable compromise between the relative benefits of self-help and the need for professional input. However, individual differences were evident in the extent to which this compromise was considered necessary and acceptable. The need for some professional contact to manage expectations and personalize therapy materials was amplified in users with OCD, given the unique features of the disorder. However, individual differences were again evident regarding the perceived value of face-to-face support. Conclusions Overall the findings demonstrate the need for flexibility in the provision of low intensity interventions for OCD, responsive to user preferences, as these preferences impact directly on engagement with therapy and perceptions of effectiveness.